El significado de la responsabilidad en el pensamiento de Hannah Arendt y su proyección en el tiempo - Cantero, María de los Ángeles (2024)
This paper analyses the variations and continuities of the meaning of responsibility in the different stages of Hannah Arendt’s work. First, it highlights the importance given to the political meaning of responsibility in the texts written before the report on the Eichmann trial. Then, it examines the mutations leading to a stress on the legal-moral meaning and on the relationship between thought, will and judgement. As a conclusion, it discusses the legacy of Arendt’s thought on responsibility and its reception by later generations.